2018
DOI: 10.1007/s00264-018-3788-z
|View full text |Cite
|
Sign up to set email alerts
|

Peri-articular injection of an analgesic mixture in primary total hip arthroplasty: an effective strategy for pain control during the first post-operative day

Abstract: Level II, cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Meta-analyses based on studies employing methylprednisolone and placebo present a significant difference in pain assessment using the VAS scale in first 48 hours postoperatively and opioid agents administered parenterally per 1 kg of body mass [2,4,6,18,20,21,[26][27][28]. Also confirmed by the present study ( Figs.…”
Section: Discussionsupporting
confidence: 84%
“…Meta-analyses based on studies employing methylprednisolone and placebo present a significant difference in pain assessment using the VAS scale in first 48 hours postoperatively and opioid agents administered parenterally per 1 kg of body mass [2,4,6,18,20,21,[26][27][28]. Also confirmed by the present study ( Figs.…”
Section: Discussionsupporting
confidence: 84%
“…St Michael’s HS [ 611 , 433 ] 2. Toronto Western HS [ 15 , 40 , 48 50 , 54 , 68 , 107 , 603 , 411 , 456 ] Winnpeg University of Manitoba [ 300 , 366 , 477 , 487 , 492 ] South America Colombia Bogota HS Universitario Fundación Santa Fe de Bogotá [ 220 , 291 , 376 , 615 ] United States of America California 1. CJRR [ 146 , 150 , 215 , 317 , 353 , 365 ] 2.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that liposomal bupivacaine has been associated with more superior outcomes in patients undergoing THR compared to traditional bupivacaine [29]. Apart from that, a considerable number of studies have reported that LIA is associated with more sufficient postoperative analgesia and less opioid consumption [30][31][32][33][34]. Furthermore, another recent study has suggested that LIA not only represents an effective method of analgesia but it also leads to a reduced length of stay in the hospital [35].…”
Section: Intraoperative Periarticular Injectionmentioning
confidence: 99%